Seedling mortality during biphasic drought in sandy Mediterranean soils - Benigno, S.; Dixon, Kingsley; Stevens, J. (CSIRO Publishing, 2014)
Climate change is increasing the frequency and intensity of drought, and seedling response to a recurrent pattern of drought stress is necessary to understand vegetation establishment patterns in particularly for ecological restoration and conservation projects. A controlled environment study investigated seedling physiological response of framework Mediterranean tree species to simulated successive droughts. Six-month-old seedlings were grown in 1.0 m tall pots to emulate deep soil profiles and subjected to a well watered treatment and a drought treatment consisting of an initial 60 day drought (water withholding), followed by 120 days of re-watering and a subsequent 60 day drought. Soil water access, soil water content, maximum root depth and xylem water potential were assessed through successive harvests. To assess seedling response to multiple droughts, gas-exchange and chlorophyll fluorescence measurements were taken every 15 days after each drought, and multiple times throughout re-watering. No seedling mortality was observed during the initial drought, whereas 100% mortality of all species occurred within 48 days of the second drought. Seedling gas exchange and water potential decreased with decreasing water availability but was dependent on the isohydric or anisohydric behaviour of individual species. An absence of sustained photoprotection during the second drought phase heightened photodamage to foliar tissues resulting in a more rapid decrease of gs and leaf water potential. Therefore, biphasic drought proved detrimental to seedling establishment by reducing physiological resilience, highlighting the severity of future climate change predictions towards the regeneration capacity of Mediterranean ecosystems.